A novel TECTA mutation causes ARNSHL. (January 2017) - Asgharzade, Samira; Tabatabaiefar, Mohammad Amin; Modarressi, Mohammad Hossein; Ghahremani, Mohammad Hossein; Reiisi, Somayeh; Tahmasebi, Parisa; Abdollahnejad, Fatemeh; Chaleshtori, Morteza Hashemzadeh
Abstract: Objective: Autosomal recessive nonsyndromic hearing loss (ARNSHL) is a genetically heterogeneous sensorineural disorder. Alpha-tectorin, which is encoded by the TECTA gene, is a non-collagenous component of the tectorial membrane in the inner ear defect of which leads to moderate to severe hearing loss (HL). Methods: 25 unrelated Iranian multiplex ARNSHL families, negative for GJB2 mutations, were recruited in this study. Clinical inspections including audiometric and otologic examinations ruled out syndromic forms. Genetic linkage analysis was performed using six short tandem repeat markers closely linked to DFNB21. Haplotype and LOD score analysis were used to confirm possible linkage. All coding exons of TECTA were subject to DNA sequencing in the linked family. Results: A novel homozygous variant (c.734G > A) was found in exon 5 of the TECTA gene in one family leading to a nonsense mutation (p.W245×). It co-segregated with HL in the family. This variant was not detected in 50 controls. All affected individuals in the family had moderate to severe HL. It full filled the criteria of a pathogenic variant. Conclusion: Our data confirms the phenotype-directed genotyping for DFNB21 deafness against the typical profound HL phenotype seen in the most families segregating ARNSHL. We recommend mutation screening of TECTA in ARNSHL families segregating moderate to severe HL phenotype.